The Importance of Job Motivation and Job Satisfaction on The Improvement of Hospital Nurses' Performance - Lewaherilla, Novalien Carolina; Hiariej, Harvey; Sijabat, Asiani; Tahapary, Grace Hubertina; Siahainenia, Ashwin (Green Publisher Indonesia, 2023)
This study aims to determine the extent to which the influence of work motivation and job satisfaction on the performance of nurses at GPM Sumber Hidup Hospital Ambon. This type of research uses a quantitative method approach. The sampling technique used was saturated sampling technique, namely all nurses at GPM Ambon Hospital, totaling 50 people. Data collection techniques using questionnaires and observations that have been tested for results. This research was processed using SPSS version 25. The types of data used in this study were primary data and secondary data. The data analysis method used in this research is descriptive analysis, instrument test, classical assumption test, multiple linear regression test and hypothesis testin. Based on the results of data analysis, the research data instrument test was declared valid and reliable. In the classical assumption test, the research results are normally distributed. In the t test (partial) it was found that work motivation (X1) has a positive effect on nurse performance (Y), job satisfaction (X2) has a positive and significant effect on nurse performance (Y).